Citrus Rootstocks and Their On-Site Evaluation - William S. Castle; James J. Ferguson (EDIS)
What rootstock to plant? That's an ever-present and always challenging question. In conversations with growers, this question is asked frequently because of problems with Swingle citrumelo, continued loss of trees on sour orange, and low solids for grapefruit grown on Smooth Flat Seville. This document is HS949, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2003.